2018
DOI: 10.1002/ppsc.201800262
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal Field Guided Dual Templating Synthesis of Functional Macro‐Microporous Carbon

Abstract: Due to the important role of porous carbon in the development of sustainable materials, the synthesis of porous carbon materials with various pore structures and pore sizes is intensively developed. But it is still not an easy task to obtain uniform porous structures at different nanoscales, let alone the hierarchical structures which combine different uniform porosity. The objective of this paper is to investigate if centrifugal field is applicable in the synthesis of ordered macro‐microporous carbon structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Chen et al [ 157 ] showed that the latex nanoparticles of two different sizes can be ordered into gradient materials in the PUC, with the concentration of smaller nanoparticles gradually decreasing and that of larger nanoparticles gradually increasing along the radius, as shown in Figure 14 . It was further shown that this method is even applicable to ternary nanoparticle mixtures [ 157 ] or a mixture of nanoparticles of completely different chemical natures, such as the mixture of latex and metal organic framework (MOF) nanoparticles [ 158 ]. Moreover, a functional gradient can be added into this structural gradient to make a double graded material, as shown by Bahner et al [ 159 ] They modified latex nanoparticles of one size with silver patches and then mixed these functionalized nanoparticles with bare latex nanoparticles of a different size.…”
Section: Ordering Of Nanoparticles In Preparative (Ultra)centrifugmentioning
confidence: 99%
“…Chen et al [ 157 ] showed that the latex nanoparticles of two different sizes can be ordered into gradient materials in the PUC, with the concentration of smaller nanoparticles gradually decreasing and that of larger nanoparticles gradually increasing along the radius, as shown in Figure 14 . It was further shown that this method is even applicable to ternary nanoparticle mixtures [ 157 ] or a mixture of nanoparticles of completely different chemical natures, such as the mixture of latex and metal organic framework (MOF) nanoparticles [ 158 ]. Moreover, a functional gradient can be added into this structural gradient to make a double graded material, as shown by Bahner et al [ 159 ] They modified latex nanoparticles of one size with silver patches and then mixed these functionalized nanoparticles with bare latex nanoparticles of a different size.…”
Section: Ordering Of Nanoparticles In Preparative (Ultra)centrifugmentioning
confidence: 99%
“…Then, the ordered bowl-like macro-microporous carbon nanoparticles were shaped with large surface area and pore volume after the calcination of the mixture of ZIF-8 NPs and polystyrene spheres. The dual porosity structures delivered higher capacity than uniform porous carbon when used as the cathodes of a lithium–oxygen cell . In addition, given the isostructural characters of ZIF-67 and ZIF-8, a chiseled core–shell ZIF-67@ZIF-8 structure can be produced by seed-mediated or epitaxial growth, and then ZIF-derived porous carbon materials with excellent properties may be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The dual porosity structures delivered higher capacity than uniform porous carbon when used as the cathodes of a lithium−oxygen cell. 19 In addition, given the isostructural characters of ZIF-67 and ZIF-8, a chiseled core−shell ZIF-67@ZIF-8 structure can be produced by seed-mediated or epitaxial growth, and then ZIF-derived porous carbon materials with excellent properties may be obtained. For example, Hu and his co-workers constructed the cobalt and nitrogen codoped carbon nanopolyhedra with hierarchically porous structure (Co, N-HCNP) via directly pyrolyzing the core−shell ZIF-8@ZIF-67 crystals.…”
Section: Introductionmentioning
confidence: 99%